Cysteine-activated hydrogen sulfide (H2S) delivery through caged carbonyl sulfide (COS) donor motifs. Issue 39 (27th April 2018) - Zhao, Yu; Steiger, Andrea K.; Pluth, Michael D.
Abstract : Cysteine-activated acrylate-functionalized thiocarbamates provide access to triggered COS/H2 S donors. Abstract : Hydrogen sulfide (H2 S) is an important biomolecule, and controllable H2 S donors are needed to investigate H2 S biological functions. Here we utilize cysteine-mediated addition/cyclization chemistry to unmask an acrylate-functionalized thiocarbamate and release carbonyl sulfide (COS), which is quickly converted to H2 S by carbonic anhydrase (CA).